2022
DOI: 10.1111/jmcb.12996
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Monetary Spillovers: The Matrix Reloaded

Abstract: for helpful comments and suggestions. The views in this paper are those of the authors and do not necessarily represent those of the Bank for International Settlements (BIS) or the Reserve Bank of Australia (RBA). All errors are our own.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 97 publications
2
15
0
Order By: Relevance
“…This first-stage IV is carried out separately for each country, instead of pooling the data across all countries, to allow the cost of borrowing in a given country to respond differentially to US monetary policy shocks. This is consistent with research documenting considerable differences in the transmission of US monetary policy shocks to foreign interest rates across countries (Kalemli-Özcan 2019, De Leo et al 2023, Kearns et al 2023). We use one-year bond yields as the monetary policy indicator, and not shorter rates (policy rate or money market rates), as the former also incorporates changes in risk premia.…”
Section: Introductionsupporting
confidence: 89%
“…This first-stage IV is carried out separately for each country, instead of pooling the data across all countries, to allow the cost of borrowing in a given country to respond differentially to US monetary policy shocks. This is consistent with research documenting considerable differences in the transmission of US monetary policy shocks to foreign interest rates across countries (Kalemli-Özcan 2019, De Leo et al 2023, Kearns et al 2023). We use one-year bond yields as the monetary policy indicator, and not shorter rates (policy rate or money market rates), as the former also incorporates changes in risk premia.…”
Section: Introductionsupporting
confidence: 89%
“…The literature on currency mismatch in country debt, including Bordo and Meissner (2006), has found that high shares of foreign currency debt leave countries more susceptible to financial crises when sudden stops occur. Kearns, Schrimpf and Xia (2020) find that, among emerging market economies, large bilateral portfolio equity flows and high debt denominated in the currency of advanced economies are associated with greater impact of monetary policy spillovers from advanced economies. Our empirical work provides further confirmation of the importance of currency mismatch in the exposure of small open economies to US monetary policy shocks, and provides conditions under which MaPs can be effective policy responses.…”
Section: Introductionmentioning
confidence: 82%
“…The second happened on March 19, 2021, when the trading range was clarified to be around ±25 basis points. 4 Existing literature finds that the spillovers from Japanese monetary policy shocks have been modest, especially compared with those from US monetary policy shocks, and more regional in nature (Buch and others 2019;Kearns, Schrimpf, and Xia 2022;Spiegel and Tai 2018). However, these studies examine the spillovers in a period when Japan has been increasingly monetarily accommodative, rather than spillovers during policy tightening.…”
Section: Yield Curve Control Movesmentioning
confidence: 99%